Systems and Procedures for Implementing Value Added Tax on Shipping Services Activities at PT Pelayaran Tonasa Lines - Qanita Mokodompis Qanita Mokodompis; Muhammad Khaedar Sahib; Muhammad Adil (Universitas Muhammadiyah Makassar, 2024)
The aim of this research is to gain an in-depth understanding of the systems and procedures for implementing value added tax (VAT) on shipping service activities at PT Pelayaran Tonasa Lines. The focus of the research is on PT Pelayaran Tonasa Lines Corporate Taxpayers. The analysis technique applied is descriptive qualitative, which makes it possible to describe in detail the characteristics and qualitative aspects related to the implementation of VAT. The data collection process was carried out through several methods. First, through interviews with related parties in the company to obtain direct views and information related to the implementation of VAT. Second, by using library methods to collect data and information from relevant sources such as books, journals and research reports related to taxation. Apart from that, direct observations were carried out to gain a deeper understanding of the implementation of VAT at PT Pelayaran Tonasa Lines. Documents available at the research site were also used as data sources. The research results show that the systems and procedures used in implementing VAT on shipping service activities at PT Pelayaran Tonasa Lines are in accordance with applicable laws and regulations. This shows that the company has complied with applicable legal provisions relating to tax aspects in its operations. Thus, this research contributes to strengthening understanding of tax practices in the shipping sector and can become a reference for improving or improving the tax system in the future